Dietary resistant starch dose-dependently reduces adiposity in obesity-prone and obesity-resistant male rats - Belobrajdic, D.P.; King, R.A.; Christophersen, Claus; Bird, A.R. (BMC, 2012)
Background: Animal studies show that diets containing resistant starch (RS) at levels not achievable in the human diet result in lower body weight and/or adiposity in rodents. We aimed to determine whether RS dose-dependently reduces adiposity in obesity-prone (OP) and obesity-resistant (OR) rats. Methods. Male Sprague-Dawley rats (n=120) were fed a moderate-fat, high-energy diet for 4 wk. Rats that gained the most weight (40%) were classified as obesity-prone (OP) and obesity-resistant (OR) rats were the 40% that gained the least weight. OP and OR rats were randomly allocated to one of six groups (n=8 for each phenotype). One group was killed for baseline measurements, the other five groups were allocated to AIN-93 based diets that contained 0, 4, 8, 12 and 16% RS (as high amylose maize starch) for 4 wk. These diets were matched for total carbohydrate content. At 0, 4 and 7 wk from the start of the study insulin sensitivity was calculated by homeostasis model assessment of insulin resistance (HOMA-IR) and adiposity was determined by dual-energy X-ray absorptiometry (DXA). At 8 wk, rats were euthanized and fat pad weights, intestinal digesta short chain fatty acid (SCFA) pools and plasma gut hormone levels were determined. Results: Obesity prone rats gained less weight with 4, 12 and 16% RS compared to 0% RS, but the effect in OR animals was significant only at 16% RS. Irrespective of phenotype, diets containing ≥8% RS reduced adiposity compared to 0% RS. Energy intake decreased by 9.8 kJ/d for every 4% increase in RS. All diets containing RS increased total SCFA pools in the caecum and lowered plasma GIP concentrations compared to the 0% RS, whereas plasma GLP-1 and PYY were increased when the diet contained at least 8% RS. Insulin sensitivity was not affected by RS. Conclusion: RS in amounts that could be potentially consumed by humans were effective in reducing adiposity and weight gain in OP and OR rats, due in part to a reduction in energy intake, and changes in gut hormones and large bowel carbohydrate fermentation. © 2012Belobrajdic et al.; licensee BioMed Central Ltd.